Theory of BCS-like bogolon-mediated superconductivity in transition metal dichalcogenides - Sun, Meng (2022)
We report on a novel mechanism of BCS-like superconductivity, mediated by a pair of Bogoliubov quasiparticles (bogolons). It takes place in hybrid systems consisting of a two-dimensional electron gas in a transition metal dichalcogenide monolayer in the vicinity of a Bose-Einstein condensate. Taking a system of two-dimensional indirect excitons as a testing ground of Bose-Einstein condensate we show, that the bogolon-pair-mediated electron pairing mechanism is stronger than phonon-mediated and single bogolon-mediated ones. We develop a microscopic theory of bogolon-pair-mediated superconductivity, based on the Schrieffer-Wolff transformation and the Gor'kov's equations, study the temperature dependence of the superconducting gap and estimate the critical temperature of superconducting transition for various electron concentrations in the electron gas and the condensate densities.